Elliptic flow of muons from heavy-flavour hadron decays at forward rapidity in Pb–Pb collisions at √sNN=2.76 TeV - Adam, J.; Adamovã, D.; Aggarwal, M.M.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahn, S.U.; Aiola, S.; Akindinov, A.; Alam, S.N.; Aleksandrov, D.; et al. (Elsevier, 2016)
The elliptic flow, v2, of muons from heavy-flavour hadron decays at forward rapidity (2.5 < y < 4) is measured in Pb–Pb collisions at √sNN = 2.76 TeV with the ALICE detector at the LHC. The scalar product, two- and four-particle Q cumulants and Lee–Yang zeros methods are used. The dependence of the v2 of muons from heavy-flavour hadron decays on the collision centrality, in the range 0–40%, and on transverse momentum, pT, is studied in the interval 3 < pT < 10 GeV/c. A positive v2 is observed with the scalar product and two-particle Q cumulants in semi-central collisions (10–20% and 20–40% centrality classes) for the pT interval from 3 to about 5 GeV/c with a significance larger than 3σ, based on the combination of statistical and systematic uncertainties. The v2 magnitude tends to decrease towards more central collisions and with increasing pT. It becomes compatible with zero in the interval 6 < pT < 10 GeV/c. The results are compared to models describing the interaction of heavy quarks and open heavy-flavour hadrons with the high-density medium formed in high-energy heavy-ion collisions.
Keywords: LHC; ALICE experiment; Pb–Pb collisions; Heavy-flavour decay muons; Elliptic flow; https://purl.org/pe-repo/ocde/ford#1.03.04